Taking the Soviet Union apart room by room : domestic architecture before and after 1991 - Malaia, Kateryna, 1988- (NIU series in Slavic, East European, and Eurasian studies., 2023)
"This book investigates what happens to domestic architecture during socioeconomic upheaval by analyzing how Soviet and post-Soviet urbanites, navigating the crisis of the collapse of the USSR, transformed their dwellings as their countries transformed around them"--